THE BEHAVIOR OF THE PRICE OF MILK TYPE C PAID TO THE MILK PRODUCERS FROM SÃO PAULO STATE CONFRONTED TO THE REALITY OF THE PRODUCERS FROM THE MICRO REGION OF MARÍLIA - RIBEIRO, Simone Goldman Batistic; OLIVEIRA, Sandra Cristina de; SCALCO, Andréa Rossi; PINTO, Leonardo de Barros (Revista Brasileira de Engenharia de Biossistemas, 2011)
The milk production is an important economic activity that provides employments and income and that stand out in national agribusiness, specifically in São Paulo State. The main of this work was to study the behavior of the monthly average price of the milk type C, paid to the milk producers from São Paulo State, by using economic information and time series techniques, in order to compare and to discuss the results of the study to the information obtained from a research made with a sample of producers from the micro region of Marília and from literature.